Posttraumatic stress disorder concerning the end of the covid-19 lockdown: A mini review - Michel Bourin (Archives of Depression and Anxiety - Peertechz Publications, 2020)
Posttraumatic Stress Disorder (PTSD) occurs generally two months after an acute stress. We challenge the opportunity to observe an increase of PTSD after the end of the confinement induced by the pandemic of covid-19. PTSD can develop in response to exposure to an extremely stressful or traumatic event, or an exceptionally threatening situation. Examples include rape, violent attack, severe accidents, sudden destruction of home or community, or harm to close relatives or friends, but as well after confinement. The present paper tries to prevent from the consequences of fear of pandemic and confinement.